2021
DOI: 10.1021/acs.jpcc.1c08013
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Selectivity of CO2 Reduction on Cu2ZnSnS4: The Effect of Exposed Termination

Abstract: With the advantage of excellent light absorption ability and earth-abundant elements, Cu2ZnSnS4 (CZTS) is widely applied in the photoelectrochemical (PEC) reduction of CO2. However, the microscopic mechanism of the CO2 conversion on CZTS is still unclear. Here, we have theoretically investigated the electronic properties of the CZTS to reveal the special bonding properties of CO2 under both exposed metal and sulfur terminations of the CZTS and the formation mechanisms of producing CO, HCOOH, and CH4 from a mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Subsequently, the wide band gaps (between 2.8 and 4.2 eV, Table S1) of the oxide layer not only severely restrict its conductivity and catalytic performance but also challenge its stability due to the loss of surface metallic active sites. In comparison, various low-melting-point metal sulfides exhibit better conductivity on account of their narrower band gap (Table S1), making them easier to serve as electrocatalysts. Moreover, recent studies have shown that the synergistic effect of metals with sulfur has better performance in the CO 2 RR to HCOOH, rivaling all the unoxidized bare low-melting-point metal catalysts. Sulfides generally exhibit abundant sulfur vacancy defects that could serve as active sites, featuring the defect-tuned localized electronic structure to boost CO 2 RR performance.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the wide band gaps (between 2.8 and 4.2 eV, Table S1) of the oxide layer not only severely restrict its conductivity and catalytic performance but also challenge its stability due to the loss of surface metallic active sites. In comparison, various low-melting-point metal sulfides exhibit better conductivity on account of their narrower band gap (Table S1), making them easier to serve as electrocatalysts. Moreover, recent studies have shown that the synergistic effect of metals with sulfur has better performance in the CO 2 RR to HCOOH, rivaling all the unoxidized bare low-melting-point metal catalysts. Sulfides generally exhibit abundant sulfur vacancy defects that could serve as active sites, featuring the defect-tuned localized electronic structure to boost CO 2 RR performance.…”
Section: Introductionmentioning
confidence: 99%
“…The complex reaction paths and product selectivity of the CO 2 RR have been widely explored. 59,60 For example, *COOH will generate three different intermediates (*CO, *HCOOH, and *COHOH) according to the different bonding methods of hydrogen, which determines the production of CO, HCOOH, and others. The *CH 3 OH and *CH 2 intermediates are generated by different hydrogenation of *CH 2 OH (C–H and O–H), which determine the formation of CH 3 OH or CH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The complex reaction paths and product selectivity of the CO 2 RR have been widely explored. 59,60 to CO 2 is beneficial to confine it within the vacancy (Fig. S3, ESI †), while the combination of the heptazine ring and COOH expands the delocalized range and further stabilizes the intermediate *COOH.…”
Section: The Mechanism Of the Co 2 Reduction Reactionmentioning
confidence: 99%
“…While when the exposed atoms are S atoms, the reduction product is a mixture of formic acid, CO, and methane at potentials less than −0.4 V (vs RHE). 87 Furthermore, Zhang et al using DFT calculations predicted that a (220) facet-suppressed kesterite CZTS could be an efficient photoelectro-integrated photocathode for formic acid production. This is supported by the fact that the (220) facet of CZTS is particularly favorable for competitive HER.…”
Section: Zno 311 Absorption Of Light and Photocorrosionmentioning
confidence: 99%
“…When the exposed atoms are Cu atoms, formic acid is the main product at potentials higher than −0.23 V (vs RHE). While when the exposed atoms are S atoms, the reduction product is a mixture of formic acid, CO, and methane at potentials less than −0.4 V (vs RHE) . Furthermore, Zhang et al using DFT calculations predicted that a (220) facet-suppressed kesterite CZTS could be an efficient photoelectro-integrated photocathode for formic acid production.…”
Section: Zinc-based Materials Applied In the Pec Co2 Reductionmentioning
confidence: 99%